PENERAPAN MODEL PEMBELAJARAN RECIPROCAL TEACHING DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR IPA DI SD MUHAMMADIYAH 1 BANDAR LAMPUNG - Novi, Ratika (Jurnal keilmuan dan Kependidikan dasar, 2024)
This study aims to determine the effectiveness of the application of the Reciprocal Teaching learning model in improving motivation and science learning outcomes at SMP N 20 Bandar Lampung. This study uses a Classroom Action Research (CAR) approach with two cycles, each involving four stages: planning, action implementation, observation, and reflection. The results showed that the application of the Reciprocal Teaching model can significantly increase students' interest, attention, participation, and learning outcomes. In the first cycle, the average student interest was 56.55%, attention 57.74%, and participation 59.52%. In the second cycle, there was an increase to 60.12% for interest, 63.09% for attention, and 64.88% for participation, reflecting more active student involvement. In addition, student learning outcomes also experienced a significant increase, with an average learning outcome in the first cycle of 54.52%, which increased to 83.21% in the second cycle, with an increase of 28.69 points. This improvement was due to improvement efforts made between the first and second cycles, which included better management time, selection of relevant materials, and implementation of more dynamic group discussions. Overall, the results of this study indicate that the Reciprocal Teaching learning model is effective in improving student motivation and learning outcomes at SMP N 20 Bandar Lampung.